MATHEMATICS LEARNING ASSESSMENT DURING THE COVID-19 PANDEMIC (A CASE STUDY OF MIDDLE SCHOOL TEACHERS IN WEST SULAWESI PROVINCE) - Fauziah Hakim; Dila Amanda; Nurfadilah Nurfadilah; Fitriani Fitriani (IAIN Ambon, 2021)
This qualitative research aimed to describe the efforts and obstacles of teachers in carrying out mathematics learning assessments during the COVID-19 pandemic. The research data were obtained from unstructured interviews with 10 middle school mathematics teachers spread across 4 districts in West Sulawesi Province. The results showed some of the efforts made by the teacher in conducting assessments, namely (1) for the cognitive domain, the teachers used several types of platforms, asked students to come to school by implementing health protocols, and used essay test form, (2) for the psychomotor domain, the teachers paid attention to students’ opinions/ comments during online learning and used performance task, and (3) for the affective domain it was done by observing students’ discipline both in collecting assignments and taking part in online learning. The obstacles faced include not all students submitting assignments and exams due to internet network problems and the emergence of teacher doubts about the originality of student work results. For psychomotor and affective assessments, teachers were very constrained because the majority of teachers only use non-video-based applications, while for psychomotor and affective assessments are usually carried out by observation.